Cigarette Smoking Among Secondary School-going Male Adolescents In Malaysia: Findings From The National Health And Morbidity Survey - Ling, Miaw Yn Jane; Rodzlan Hasani, Wan Shakira; Mohd Yusoff, Muhammad Fadhli; Abd Hamid, Hamizatul Akmal; Lim, Kuang Hock; Tee, Guat Hiong; Baharom, Nizam; Ab Majid, Nur Liana; Robert Lourdes, Tania Gayle; Mat Rifin, Halizah; Saminathan, Thamil Arasu (SAGE Publications, 2024)
Indexed by WOS/Scopus/ERA